Assessment of hand hygiene knowledge and practices among undergraduate nursing students at a Public Sector Nursing College, Jamshoro - Farzana Parveen; Tasleem bibi; Altaf hussain; Sabiha Sarwar; Irum Qureshi; Hafsa Bibi (Medical Journal of South Punjab, 2024)
Objective: To assess the knowledge and practice of hand hygiene among undergraduate students of nursing at a Public Sector Nursing College JamshoroMethods: A Quantitative descriptive cross sectional study was carried out from August to September 2023 at Nursing College Jamshoro. A total of 96 study participants in the study. A non-convenience sampling method was used and data was collected after departmental approval, before collection of data form the participants written informed consent was taken. The data was collected using the WHO "Hand Hygiene Knowledge Questionnaire."Results: The mean age was 22.9 ±1.8. Most respondents (71%) were in their third year of study, and most participants (70.4%) were hostel residents. Most of the respondents' source of knowledge for hand hygiene was lectures (68.8%, n = 68), and most participants (92.7%) said that hand hygiene is very significant way in prevention of infection. The majority of the participants (89.6%) said that hand rubbing is required prior to administering an injection to a patient. Majority of the responded (89.6%) reported that wearing jewelry increased the risk of colonization of hands with pathogens.Conclusion: The present study reported good knowledge and practice of hand hygiene among nursing undergraduates. It also demonstrated that they had been adequately exposed to information about hand hygiene.